Factors influencing researchers’ scientific integrity in scholarly publishing: a path analysis approach - Lan Thi Nguyen; Kulthida Tuamsuk (Research Ethics Review)
Scientific integrity is defined as the condition that occurs when individuals adhere to accepted standards, professional values, and practices of the relevant scientific community. This study aims to investigate the influential factors on the scientific integrity in scholarly publishing of researchers in Thailand. The questionnaire was delivered to a sample size of 398 top researchers who had high citations and h-index recorded in the Scopus database during the past 5 years, 316 responses were returned. The findings confirm that there are five factors that affect scientific integrity in scholarly publishing: university/faculty requirements/policies, university support, aspects of publishing, publisher aspects, and researcher-related factors. It is evident that establishing a process and criteria for authorship agreement and verification, as well as dedicating offices or units within the university to address research integrity concerns and provide support to researchers, exhibit the highest factor loading values. The findings ensure that scientific integrity stands out as a top priority for researchers linked with prominent research universities in Thailand. To tackle this challenge, it is recommended for the universities to prioritize initiatives aimed at enhancing researchers’ ethical awareness and nurturing scientific integrity.